Obtención de papel kraft a partir de la fibra de dos variedades de Agave (Americana L. – Cabuya negra y Sisalana perrine – Cabuya blanca) con dos sustancias químicas (Carbonato de calcio y Sulfato de sodio) para la cocción y dos métodos de blanqueo con (Dióxido de cloro y Agua oxigenada) en el laboratorio de Agave de la Carrera de Ingeniería Agroindustrial de la Universidad Técnica de Cotopaxi - Pérez Escobar, Josué Israel (2016)
The Technical University of Cotopaxi with coordination to Agricultural Engineering Career and Researching Direction carried out the kraft papper obtainment process which had two day process from the moment the fiber gets wet to improve its characteristics and softeness after the cooking process, liquefied, sheet formation, pressing and drying. Two outstanding treatments were obtained on the investigation that meet the physical ranges by 1 429 INEN regulation. As the treatment case is: t7 (Sisalana agave fiber, calcium carbonate, chlorine dioxide). Meet with the indicators and objectives.